2022
DOI: 10.1128/spectrum.01158-21
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Degeneration and Reduction in the Fish Pathogen Mycobacterium shottsii

Abstract: Morone saxatilis (striped bass) is an ecologically and economically important finfish species on the United States east coast. Mycobacterium shottsii and Mycobacterium pseudoshottsii were originally described in the early 2000s as novel species from outbreaks of visceral and dermal mycobacteriosis in this species. Biochemical and genetic characterization place these species within the Mycobacterium ulcerans / M. mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…However, M. shottsii is mainly isolated from striped bass ( Morone saxatilis ) and causes visceral and dermal mycobacteriosis in fishes; human diseases caused by M. shottsii have not been reported yet. 8 …”
Section: Discussionmentioning
confidence: 99%
“…However, M. shottsii is mainly isolated from striped bass ( Morone saxatilis ) and causes visceral and dermal mycobacteriosis in fishes; human diseases caused by M. shottsii have not been reported yet. 8 …”
Section: Discussionmentioning
confidence: 99%
“…Although the ANI values agree with regard to their synonymy, the aforementioned species are regarded as different species on the basis of different clinical features, host spectra, and pathogenicity ( 16 ). Nevertheless, the characteristic multiple copies of IS 2404 /IS 2606 in M. pseudoshottsii and M. ulcerans and IS Mysh01 /IS Mysh03 specific to M. shottsii were absent from 050012 ( 3 , 17 , 18 ), confirming that it was M. marinum .…”
Section: Announcementmentioning
confidence: 92%
“… Mycobacterium marinum is an opportunistic human pathogen ( 1 ) and is closely related to Mycobacterium ulcerans , Mycobacterium pseudoshottsii , and Mycobacterium shottsii ( 2 4 ). Here, we report the complete genome sequence of M. marinum strain 050012.…”
Section: Announcementmentioning
confidence: 99%
“…The pathogen has a close genetic relationship with M. tuberculosis , the causative agent of tuberculosis in humans (Stinear et al, 2008). Together with M. ulcerans , M. ulcerans ecovar Liflandii , M. shottsii , and M. pseudoshottsii , M. marinum constitutes the M. ulcerans / M. marinum complex (MuMC), which is very closely related to other MuMC members (Doig et al, 2012; Gauthier et al, 2022). Furthermore, Das et al (2018) suggested that M. marinum strains should be divided into the two subspecies, the “Aronson‐lineage” M .…”
Section: Introductionmentioning
confidence: 99%
“…moffett based on the whole‐genome analyses. The “Aronson‐lineage” includes laboratory variants (i.e., CCUG20998, NCTC2275, and 1218R) of the M. marinum type strain that was isolated from fish in USA, and the “M‐lineage” includes M. marinum M, a strain from a human patient, as well as M. ulcerans , M. ulcerans ecovar Liflandii , and M. pseudoshottsii (Das et al, 2018; Gauthier et al, 2022).…”
Section: Introductionmentioning
confidence: 99%